THE EFFECT OF QUR’ANIC MEMORIZATION LEARNING ON STUDENTS’ QUR’ANIC READING AND MEMORIZATION SKILLS - Yola Novriyana; Nurlaili; Suhirman (El Midad, 2025)
This study aims to analyze the effect of Qur’anic memorization learning on students’ abilities in reading and memorizing the Qur’an. The specific objectives are: (1) to determine the effect of Qur’anic memorization learning on the reading ability of fourth-grade students at SDN 09 Religious Model School, Bengkulu City; (2) to examine its effect on students’ memorization ability; and (3) to assess its overall impact on both reading and memorization skills. The research employed a quantitative method with an associative approach. Data were collected through questionnaires and analyzed using total sampling, basic and classical assumption tests, simple linear regression, and t-tests. The population and sample consisted of 61 students. The findings revealed that Qur’anic memorization learning significantly affects students’ Qur’anic reading ability (37.6%), memorization ability (42.1%), and the combined ability to read and memorize the Qur’an (53.6%). These results highlight the importance of integrating memorization-based approaches in improving students’ Qur’anic literacy and retention skills